Sifat Wanita Salihah Menurut Syekh Utsaimin - Waskito, Subarkah Yudi; saffanah, saffanah (Izzatuna: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Salihah women have very noble values ​​in Islam. The title as a pious woman is a dream for every woman. If being a pious woman is a dream for every woman, then of course the woman must meet the demands of the Shari'a, have the qualifications that have been determined by the Shari'a as a determining condition in order to be included in the category of a pious woman. This study describes the characteristics of pious women contained in Surah Al-Ahzab and explains its implications for the modern era. The collection in this study uses a type of library research (Library Search). The results of this study indicate that a pious woman will always maintain her behavior and speech, she will not do anything but act according to the guidance of the Shari'a, as well as will not say if the word contains badness. Shaykh Utsaimin rahimahullah interprets that in QS. Al-Ahzab: 35 contains the characteristics of righteous women and righteous men, the verse also contains similarities between men and women in terms of carrying out Allah's law.